The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1177/039463200601900209
|View full text |Cite
|
Sign up to set email alerts
|

Role of FK778 Alone or in Combination with Tacrolimus or mTOR Inhibitors as an Immunomodulator of Immunofunctions: In Vitro Evaluation of T Cell Proliferation and the Expression of Lymphocyte Surface Antigens

Abstract: We evaluated the in vitro capacity of FK778, alone or in combination with other immunosuppressive drugs: Tacrolimus (TRL); Sirolimus (SRL), Everolimus (EVL), to inhibit clonal expansion of Tlymphocytes and expression of lymphocyte-activation surface antigens; secondly, we compared the immunosuppressive potential of FK778 combined with TRL, SRL and EVL with the same combinations using Mycophenolic acid (MPA) as antimetabolite. Lymphocyte proliferation was assessed by 3H_ Thymidine incorporation, in whole blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recently, we found that BALB/c mice infected with E. granulosus respond by producing serum MCP-1 as early as 10 days post infection and we determined the serum MCP-1 and MIP-2 levels as indicators for the inflammatory process (39)(40)(41)(42). Other studies have demonstrated that mice infected orally with T. spiralis larvae develop quantitative and functional changes in the peritoneal macrophage population (43,44). These macrophages inhibit DNA synthesis of syngeneic and allogeneic tumor cells and kill EL-4 tumor cells, properties attributed to activated macrophages.…”
Section: Nk Cells and Parasitesmentioning
confidence: 94%
“…Recently, we found that BALB/c mice infected with E. granulosus respond by producing serum MCP-1 as early as 10 days post infection and we determined the serum MCP-1 and MIP-2 levels as indicators for the inflammatory process (39)(40)(41)(42). Other studies have demonstrated that mice infected orally with T. spiralis larvae develop quantitative and functional changes in the peritoneal macrophage population (43,44). These macrophages inhibit DNA synthesis of syngeneic and allogeneic tumor cells and kill EL-4 tumor cells, properties attributed to activated macrophages.…”
Section: Nk Cells and Parasitesmentioning
confidence: 94%